Efficacy of immunosuppressive treatment in a systemic lupus erythematosus patient presenting with inclusion body myositis. (5th April 2016) - Varela-Rosario, Noemí; Pérez-Berenguer, Juan L; Vilá, Luis M
Abstract : Inclusion body myositis (IBM) is an inflammatory myopathy that is generally unresponsive to immunosuppressive drugs. The coexistence of IBM with other autoimmune connective tissue diseases is rare. We present a case of a 76-year-old woman with systemic lupus erythematosus (SLE) who developed proximal muscle weakness of lower extremities and mild elevation of serum creatine kinase (CK) at 495 U/L. Muscle biopsy showed changes of endomysial inflammation and rimmed vacuoles consistent with IBM. She was treated with prednisone 40 mg daily and methotrexate 12.5 mg weekly. One month later, her physical examination showed minimal proximal weakness of lower extremities. CK levels decreased to 44 U/L. Prednisone dose was gradually decreased to 5.0 mg daily. She remained stable with normal CK levels during a follow-up period of 10 months. This case, together with other reports, suggests that IBM in the setting of SLE represents a different subtype that can benefit from immunosuppressive treatment.